Influence of coach's leadership behaviour and process of training on performance and competition efficacy on elite sport - Trninic, M.; Papic, V.; Trninic, V. (Acta Kinesiologica, 2009)
Coach's leadership behaviour and the training process in a certain type of sports are primarily related to selective decision-making, knowledge transfer, motivational techniques and guidance and preparation of an individual and/or group towards reaching set goals. An expert coach who has an appropriate relationship with an athlete creates a two-way and reciprocal interaction in a sports context. Each athlete has his mode of training and adequate reactions to different models of leadership. There is an empirical support to the claim that performance and competition efficacy are determined by coach's behaviour and the training process. Parallely, coach's leadership behaviour must be synchronised with the characteristics of athletes and situational determinants. In order for a leadership model to be successful, it is necessary to apply a system of integrative evaluation of genetic potential and total efficacy in a certain sport, and also to apply methodics of integral sports preparation. While doing so, it is of high importance for appropriate modelling of the sports preparation process to connect the objective and subjective personality and motivational structure evaluation of the athlete. Therefore, the task of the coach is establishing and recognising athlete's characteristics and adapting leadership behaviour and training process not only to the state of an individual and a group, but also to the situation, goals and development of the athlete's career. Also, the role of the coaching team in the growth of talented athletes is to enable a quality cooperation of different profiles of experts, that is, to apply a transdisciplinary approach in which the role of the head-coach and his associates is to find the best way to develop the overall potential of the athlete and the entire team.